PULSATIONAL ACTIVITY OF THE SMALL–AMPLITUDE CEPHEID POLARIS (α UMi) IN 2016-2017 - Usenko, I. A.; Kovtyukh, V. V.; Miroshnichenko, A. S.; Danford, S. (Одеські астрономічні публікації, 2017)
We present the results of an analysis of 49 spectra of α UMi (Polaris) obtained during August – December 2016 and January – March 2017. Frequency analysis displays an unexpected decrease of the pulsational period up to 17.3 min in comparison to the 2015 observational set. The radial velocity amplitude was reduced to 3.43 km s−1 in 2016 and to 3.31km s−1 in the beginning of 2017 in comparison with 4.16 km s−1 in 2015. This result is also unexpected, because during the last decade a gradual amplitude growth has been observed. The average Teff = 6021 K determined from the 2016–2017 data is close to the values determined for the 2001–2015 set.